2004
DOI: 10.1007/s00253-003-1409-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CreA in glucose and xylose catabolism in Aspergillus nidulans

Abstract: The catabolism of glucose and xylose was studied in a wild type and creA deleted (carbon catabolite de-repressed) strain of Aspergillus nidulans. Both strains were cultivated in bioreactors with either glucose or xylose as the sole carbon source, or in the presence of both sugars. In the cultivations on single carbon sources, it was demonstrated that xylose acted as a carbon catabolite repressor (xylose cultivations), while the enzymes in the xylose utilisation pathway were also subject to repression in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Interestingly, Mach-Aigner et al also reported an increase in the abundance of the xyr1 transcript during incubation with another hemicellulose monomer, D-xylose, but interpreted this increase as due to carbon catabolite derepression (19). We consider this interpretation flawed, because D-xylose has been shown to be a carbon catabolite-repressing carbon source in Saccharomyces cerevisiae (6) and Aspergillus nidulans (26). We admit that proof for D-xylose as a carbon catabolite-repressing carbon source in T. reesei has not yet been published, but its operation can be deduced from the fact that cultivation of T. reesei on D-xylose does not even lead to the low cellulase levels that are formed during carbon catabolite derepression (28).…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, Mach-Aigner et al also reported an increase in the abundance of the xyr1 transcript during incubation with another hemicellulose monomer, D-xylose, but interpreted this increase as due to carbon catabolite derepression (19). We consider this interpretation flawed, because D-xylose has been shown to be a carbon catabolite-repressing carbon source in Saccharomyces cerevisiae (6) and Aspergillus nidulans (26). We admit that proof for D-xylose as a carbon catabolite-repressing carbon source in T. reesei has not yet been published, but its operation can be deduced from the fact that cultivation of T. reesei on D-xylose does not even lead to the low cellulase levels that are formed during carbon catabolite derepression (28).…”
Section: Discussionmentioning
confidence: 62%
“…When the mutant was grown on the mixture of glucose and xylose, it was observed that both sugars were taken up from the medium simultaneously, but glucose was consumed at a specific rate that was threefold that of xylose. Earlier it was reported that, when a reference strain was grown on a mixture of glucose and xylose, there was a sequential utilization of the two sugars (the xylose was only catabolized after the glucose had been depleted) (Prathumpai et al, 2004), and for that reason the cultivation of the reference strain on the sugar mixture was not pertinent to our study.…”
Section: Physiological Parameters and Metabolism Of Polyolsmentioning
confidence: 67%
“…Thus, manipulation of the expression or activity of the regulators CreA, XlnR or PacC (either alone or in combination) could be exploited to improve the production of target proteins, the expression of which is driven by xylanolytic promoters. In this regard, the creA d 30 mutation has been shown to result not only in considerably elevated transcript levels of the xylanolytic genes under inducing conditions but also in elevated levels of extracellular xylanase activity [29,30]. This could well be a result of the derepression of the regulatory gene xlnR [18].…”
Section: Introductionmentioning
confidence: 99%